IMPLEMENTASI NILAI-NILAI PENDIDIKAN ISLAM DALAM KONTEKS MODERN: TINJAUAN TERHADAP PRAKTIK DAN TANTANGAN - faizin, faizin; Helandri, Joni; Supriadi, Supriadi (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
The purpose of this study is to analyze the assimilation of Islamic educational ideas in a contemporary setting, as well as to evaluate the approach that is taken and the challenges that are involved with this endeavor. The significance of having a comprehensive understanding of how Islamic principles might be implemented in educational settings is expanding in parallel with the process of globalization and the advent of technology. The research technique makes use of a qualitative approach, which includes conducting in-depth interviews and making observations of Islamic educational institutions as well as other important stakeholders. The examination sheds light on the successes and challenges that have been encountered in the process of introducing Islamic concepts into the modern curriculum, as well as the instructional methods that have been utilized and the challenges that have been faced while attempting to integrate these principles in surroundings that are culturally and technologically diverse. The outcomes of the research provide an essential understanding of the implementation of Islamic education within a contemporary framework. In respect to Islamic principles in the modern day, the purpose of this research is to investigate the potential impact that Islamic principles could have on the curriculum, learning practices, and the development of student character.